Human capital and economic growth - challenges and prospects for the Nigerian economy - Subramanian, Lakshmy; Constantinos Alexio, Constantinos; Nellis, Joseph G.; Steele, Pamela; Tolani, Foyeke (B&ESI, 2019)
Despite its recent policy reorientation towards capital accumulation as a means of boosting economic activity, Nigeria still faces low productivity, poor infrastructure, and underdeveloped human capital. In this paper, we review the challenges to Nigeria’s development and explore the impact of human capital on economic growth over the period 2011 to 2017. To that purpose, Granger Causality Tests has been adopted to establish the causal dimension between human capital and economic growth. While we provide some tentative evidence on the contribution of human capital to economic growth, we also highlight key strategic questions that, when addressed, could provide some solutions to the existing pressing issues.
Keywords: Physical capital; Growth and development; Human capital; Granger Causality